Impact of Heterogeneous Environmental Regulation on Manufacturing Sector Green Transformation and Sustainability - Liu, JianHua; Wang, HuiYang; Ho, HollyWenWei; Huang, Liangchao (Frontiers in Environmental Science, 2022)
This paper aims to investigate the effect of heterogeneous environmental regulation on the green transformation of the manufacturing sector in the Yellow River Basin by using the SBM-GML. Spatial econometrics and threshold regression models were utilized to examine the effect of heterogeneous environmental regulation on the green transformation of the manufacturing sector in the Yellow River Basin and the regulatory function of green technology innovation. The results demonstrated that the green total factor productivity (GTFP) of the manufacturing sector in the Yellow River Basin increased with fluctuations from 2010 to 2019. The analysis revealed a U-shaped relationship between command-and-control type environmental regulation and the green transformation. It also signifies that market-incentive type environmental regulation had a negligible effect on the green transformation. The relationship between public-participation type environmental regulation and the green transformation of the manufacturing sector in the Yellow River Basin was “U”-shaped but inverted. Innovations in green technology are a significant variable that influences the heterogeneous environmental regulations that affect the green transformation.